One-part geopolymers versus Ordinary Portland Cement (OPC) mortars : durability assessment - Abdollahnejad, Zahra (2013)
Investigations on the field of geopolymeric binders, state that this new material is likely to have high potential to become an alternative to Ordinary Portland cement (OPC). Recent results on the Life Cycle Analysis (LCA) of geopolymers they have a lower impact on global warming than OPC but on the other side they have a higher environmental impact regarding other impact categories. Lower CO2 emissions geopolymers are therefore needed. Classical two part geopolymers could be made more eco-efficient with a lower carbon dioxide footprint if the use of sodium silicate is avoided. Besides current geopolymeric mixes can suffer from efflorescence originated by the fact that alkaline and/or soluble silicates that are added during processing cannot be totally consumed during geopolymerisation. Therefore new and improved geopolymer mixes are needed. One-part geopolymers (sodium silicate free) were described by the first time in 2008 still a lot of issues remain unexplained about them. This paper compares the durability performance of one-part geopolymers with OPC mortars. The obtained results revealed that replacing 70% Portland cement by 58.3% Fly ash, 4% calcined stuff and 7.7% calcium hydroxide results in satisfactory and promising results in durability tests.